A Computational Bibliometric Analysis of E-Groceries Analysis Using VOSviewer - Lesmana, Rudhi; Rifaldi, M Ihsan (Universitas Komputer Indonesia, 2023)
The purpose of the research is to combine mapping analysis with VOSviewer as well as Publish or Perish software to do a computerized bibliometric analysis of the topic